Inter-religious dialogue and contemporary peace- building: from hostility to mutual respect and better understanding - Shehu, Fatmir Mehdi (2014)
The misunderstanding and misinterpretation of religion and its teachings by its followers and others have given the impression that religion is the sole source of all past and current conflicts faced by humanity. This assumption is perhaps encouraged due to the limited knowledge of other religions and the wrong impression spread because of peoples‟ ignorance of their own religion. The media presents religion with stories focused exclusively on hatred, war-making, and devastation. However, the value of peace has been considered as the core principle in the teachings of major world religions. The ongoing inter-religious activities initiated by both, religious individuals and institutions have shown very clearly that religion stands for peace and not war. This research sees inter-religious dialogue as the most important element on which the notion of peacebuilding stands. This study attempts to show that inter-religious activities are a great resource for building and sustaining peace between people of different socio-cultural and religious backgrounds in the long term. The paradigm of inter-religious dialogue is to provide people with a better understanding of religion and its teachings and should shift their views from hostility and enmity to mutual respect and better understanding. Descriptive and analytical methods will be employed by the researcher with the intention of providing findings that will serve as solid solutions for the contemporary conflicts witnessed by our contemporary societies.